Investigating the Use of Instructional Language in English Language Teaching - Luthmailia, Shadia; Jismulatif; Supriusman (IKIP Siliwangi, 2025)
This research aims to analyze the use of the language of instruction in English language teaching at SMA Negeri 5 Mandau, as well as students' perceptions of the use of the language of instruction. This research used a descriptive qualitative method approach and involved three teachers and fifteen grade XI students selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using the Miles and Huberman flow model. The findings showed that the language of instruction most often used by teachers was mixed language (English and Indonesian) to facilitate students' understanding of the material taught. Students supported using mixed language because it helped them understand the material better, enriched vocabulary, created a more comfortable learning atmosphere, and reduced anxiety in the learning process. In addition, over-reliance on the mother tongue could hinder the development of students' English language skills. In conclusion, a balanced use of mixed language could improve the effectiveness of English language teaching while accelerating students' language acquisition.